Elucidation of the biosynthetic pathway of cis-jasmone in Lasiodiplodia theobromae - Ryo Matsui (Nature Portfolio, 2017)
Abstract In plants, cis-jasmone (CJ) is synthesized from α-linolenic acid (LA) via two biosynthetic pathways using jasmonic acid (JA) and iso-12-oxo-phytodienoic acid (iso-OPDA) as key intermediates. However, there have been no reports documenting CJ production by microorganisms. In the present study, the production of fungal-derived CJ by Lasiodiplodia theobromae was observed for the first time, although this production was not observed for Botrytis cinerea, Verticillium longisporum, Fusarium oxysporum, Gibberella fujikuroi, and Cochliobolus heterostrophus. To investigate the biosynthetic pathway of CJ in L. theobromae, administration experiments using [18,18,18-2H3, 17,17-2H2]LA (LA-d5), [18,18,18-2H3, 17,17-2H2]12-oxo-phytodienoic acid (cis-OPDA-d5), [5′,5′,5′-2H3, 4′,4′-2H2, 3′-2H1]OPC 8:0 (OPC8-d6), [5′,5′,5′-2H3, 4′,4′-2H2, 3′-2H1]OPC 6:0 (OPC6-d6), [5′,5′,5′-2H3, 4′,4′-2H2, 3′-2H1]OPC 4:0 (OPC4-d6), and [11,11-2H2, 10,10-2H2, 8,8-2H2, 2,2-2H2]methyl iso-12-oxo-phytodienoate (iso-MeOPDA-d8) were carried out, revealing that the fungus produced CJ through a single biosynthetic pathway via iso-OPDA. Interestingly, it was suggested that the previously predicted decarboxylation step of 3,7-didehydroJA to afford CJ might not be involved in CJ biosynthesis in L. theobromae.